Manners at works corporate etiquette - Schrank, Louise Welsh; Stage Fright Productions; Learning seed (Lake Zurich, Ill. : Learning Seed, 2006)
Discussions & vignettes covering the proper way to behave in business situations. Courtesy puts people at ease, makes them comfortable & contributes to professional success. Covered are introductions & hand shakes, smoking, appearance & clothing, eating, promptness, small talk, telephone etiquette, etc.
Narrator : Leslie Gray
For middle secondary to senior secondary students
Keywords: Business etiquette; Manners and customs; Etiquette